2023
DOI: 10.1007/s00405-023-08038-1
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of the Niigata PPPD Questionnaire in a Western population

Abstract: Purpose To analyze the psychometric properties of the Niigata Questionnaire (NPQ) for use in a European population with persistent postural-perceptual dizziness (PPPD). Methods Observational study included 140 patients with different vestibular conditions. Construct validity, internal consistency and concurrent validity were analyzed. Intra-class correlation coefficient (ICC), standard error of measurement (SEM) and minimal detectable change (MDC) were cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
2
3
0
Order By: Relevance
“…The results strongly confirmed our predictions with the highest NPQ scores for the PPPD group, the second highest for the vestibular group, and the control group having the lowest NPQ scores, similarly to Yagi et al [31]. Our ROC curve analysis showed that NPQ was a significant but poor predictor of PPPD, similar to a ROC curve analysis by Castillejos-Carrasco-Muñoz et al [6], but poorer than the original analysis by Yagi et al [31].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The results strongly confirmed our predictions with the highest NPQ scores for the PPPD group, the second highest for the vestibular group, and the control group having the lowest NPQ scores, similarly to Yagi et al [31]. Our ROC curve analysis showed that NPQ was a significant but poor predictor of PPPD, similar to a ROC curve analysis by Castillejos-Carrasco-Muñoz et al [6], but poorer than the original analysis by Yagi et al [31].…”
Section: Discussionsupporting
confidence: 90%
“…Our study aimed to better understand the symptoms of patients with PPPD and to validate the NPQ in a Western French speaking population. Our participant pool aligned perfectly with previous literature suggesting a higher percentage of women than men suffering from PPPD and an age range of 30−50 years [6,26,28].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations